Advantages of using a nanomodified mesh with an antiseptic in the surgical treatment of abdominal hernia - Ruslan Lutkovskyi (Kazimierz Wielki University, 2022)
Surgical treatment of open operations for abdominal hernias (AH) using classic techniques of allogeneoplasty (sublay, onlay) is often accompanied by an increase in intra-abdominal pressure (IBP) and a decrease in the volume of the abdominal cavity, which in the postoperative period leads to abdominal compartment syndrome (ACS) In 2 ,4 - 3.6% of cases and mortality in 1.2 - 3.4% of observations. This requires a special method of closing a large defect of the abdominal wall, which would not increase ICP. The use of improved techniques contributes to the creation of the optimal volume of the abdominal cavity and improves the results of treatment, in particular, the frequency of ACS decreases. But it should be noted that the use of combined operations with a classic polypropylene mesh leads to a high frequency of complications from the postoperative wound, such as seroma (30.8 - 60.4%), suppuration of the postoperative wound (4.8 - 6.4%), ligature fistula (1.2 - 3.0%), meshoma (0.06 - 1.60%). Aim - to improve the results of surgical treatment of abdominal hernias (AG) when using a nanomodified polypropylene mesh with an antiseptic. Materials and methods. An analysis of surgical treatment of 400 patients with GJ was carried out. Depending on the type of mesh implant used during surgical treatment, patients were divided into two groups. 200 (50%) patients of group I underwent surgery using a nanomodified polypropylene mesh with an antiseptic, in group II, 200 (50%) patients underwent surgery using a classic polypropylene mesh. Results and discussion. Statistically significantly better results were obtained in patients of group I compared to group II. Thanks to the fact that in patients of group I, a nanomodified polypropylene mesh implant with an antiseptic was used, it was possible to achieve a reduction in the frequency of seroma by 4.2 times, suppuration of the postoperative wound by 8 times, inflammatory infiltrate by 10 times, and the occurrence of ligature fistulas of the anterior abdominal wall by 12.5 times, meshomas in 7.5 times. The long-term results of surgical treatment of AG also confirm the advantages of operations for abdominal hernias using nanomodified polypropylene mesh with an antiseptic compared to the use of classic polypropylene mesh, which is associated with a decrease in the frequency of wound infectious complications, migration and shrinkage of the mesh and prevents recurrence of AG. The duration of inpatient treatment in group I was (7.0±1.0) days, in group II - (12.0±2.2) days. Conclusion. Surgical treatment of abdominal hernias using a nanomodified polypropylene mesh with an antiseptic is more effective compared to the use of a classic polypropylene mesh, as evidenced by a decrease in the frequency of seroma from (30.5±1.2) to (7.3±0.5)%, suppuration postoperative wound - from (9.8±0.5) to (1.2±0.2)%, inflammatory infiltrate - from (12.2±0.6) to (1.2±0.2)%, ligature fistulae of the anterior abdominal wall - from (6.5±0.5) to (0.5±0.1)%, meshomas - from (3.9±0.3) to (0.5±0.1) %, chronic postoperative pain - from (8.0±0.6) to (1.3±0.2)%, hernia recurrence - from (9.3±0.6) to (1.3±0.2 )%.